RETRACTION Latino, F., Limone, P. ., Peluso Cassese, F., Martinez-Roig, R., Amato, G., & Tafuri, F. (2025). Deportistas de doble carrera y estrés psicofisiológico. Retos, 63, 693–704. https://doi.org/10.47197/retos.v63.111368 - RETOS, RETOS (Retos, 2025)
Latino, F., Limone, P. ., Peluso Cassese, F., Martinez-Roig, R., Amato, G., & Tafuri, F. (2025). Deportistas de doble carrera y estrés psicofisiológico. Retos, 63, 693–704. https://doi.org/10.47197/retos.v63.111368 Retraction of the article by the editor of the journal. There has been a number of clear and conclusive pieces of evidence that they include references that are not related to the topic of the article or the context in which they are cited. The pattern discovered is that the authors have been self-citing their work, in all the articles that are retracted, without any relation to the content of the article in question, introducing citations that are not related to the text and then adding the corresponding references to these citations in the reference list.